The Effectiveness of Using Vidio Vlog on Students Vocabulary Mastery For Grade 8 Junior High School Students' at SMP Advent Sei Bamban - Kitche Vetricya Sarumpaet; Nelson Balisar Panjaitan (Peneliti.net, 2022)
This study aims to determine the impact of video vlog on student’s vocabulary mastery for grade 8 junior high school students at SMP ADVENT Sei Bamban. The research method used is experimental research methods. Data were collected using pre-test and post-test where divided into two research classes; experiment and control group. As many as 16 students being in experiment group also 16 students in control group. In calculating the effectiveness of using video vlog on students vocabulary mastery for grade 8 junior high school students at SMP ADVENT Sei Bamban, researchers used Normalized Gain (N-Gain). The data analysis technique was assisted by SPSS. The results showed that the average value of the N-gain score for the experimental class is 81.553 or 81.5% which is included in the category of very effective. Meanwhile,The average N-gain score for the control class is 50.3744 or 50% is included in the effective enough category. Based on the result, it can be concluded that the use of video vlog on student’s vocabulary mastery for grade 8 junior high school students at SMP ADVENT Sei Bamban is very effective to improve students’ vocabulary mastery. This research can be a helpful teaching methods for teacher in teaching vocabulary to students.